A clash of space. Reaccessing spaces and speech : a cognitive-linguistic approach to Psalm 2 - Bruyn, Joseph de (Journal for Semitics, 2013)
Applying cognitive linguistics to the text of Psalm 2 is shown to be indispensable for a more comprehensive understanding of this psalm. Studying the poet's use of cognitive concepts such as "heaven" and "earth", as well as his reference to Zion and certain body-parts, makes it possible to reconstruct the psalm as a form of "body-cosmology". In this exegetical structure, Psalm 2 can be described as a liturgical poem which was possibly recited during the anointing ceremonies of the Judean kings. Here, a mere human being is re-created as the "son of Yahweh" to rule as an extension of Yahweh's "god-space" over "that-which-is-below". Any rebellion from within "earthly space" will be dealt with by Yahweh himself.
paid